THE COMPARATIVE STUDY OF ADRAKADI QUATH SIDHA DUGDHA AND ASHWAGANDHA CHURNA IN THE MANAGEMENT OF ARSHAS (HEMORRHOIDS) - B Jondhale, Pradeepkumar; Atram, Surekha (International Journal of Ayurveda and Pharma Research, 2015)
Arshas (hemorrhoids) occurs mainly due to the vitiation of Agni, which leads to Malavasthambha (constipation) and Vimarga gamana of Apana Vayu. So obviously, the drug, which has capacity to streamline the vitiated Agni and regulate the Anulomagati of Apana Vayu, will be the drug of choice in treating Arshas. Adrakadi quath sidha dugdha possesses Ushna, Tikshna Dipana, Pachana and Vatanulomana property. Envisaging these points an attempt has been put forth to evaluate the efficacy of Adrakadi quath sidha dugdha in patients suffering from Arshas and the subject entitled The Comparative study of Adrakadi quath sidha dugdha and Ashwagandha churna in the management of Arshas w.s.r. to hemorrhoids have been selected for study. Total 60 patients of Arshas were registered for the present study. The selected patients were distributed randomly into two groups. Group A: 30 patients were treated with Adrakadi quath sidha dugdha 40 ml twice a day with water, after food for 15 days. Group B: 30 patients were treated with Ashwagandha churna 2 gm twice a day with water for 15 days. The observations and results obtained from clinical study have been analysed statistically to evaluate the significance of the curative properties of therapies.